Physical activity reduced hypertension in the elderly and cost-effective - Gandasentana, Robert D.; Kusumaratna, Rina K. (Universa Medicina, 2011)
Sedentary lifestyle gives rise to important health problems in the world, such as cardiovascular disorders and hypertension. Hypertension is an important modifiable risk factor for cardiovascular disease and is the most significant risk factor for stroke. There is mounting evidence that physical activity is beneficial for the elderly, and may have positive effects on chronic disorders, such as hypertension. The purpose of the present study was to assess the effectiveness of physical activity for reducing hypertension and the healthcare costs of hypertension in the elderly. This cross-sectional study, conducted from August to October 2009, involved 237 community-dwelling elderly in one district of South Jakarta, comprising 86 males and 151 females aged 66.4 Â± 6.3 years. Data on background characteristics were collected using a validated questionnaire, while physical activity was assessed using the short version of the International Physical Activity Questionnaire. Results showed that 32.9% elderly was physically active and 67.1 % less physically active. The overall prevalence of hypertension was 18.6%, while there was no significant difference of hypertension between male and female elderly (p=0.737). The risk for hypertension in the physically active group was 0.40 times lower than that in the less physically active group (OR = 0.40; 95% C.I. 0.16 â€“ 0.97), leading to annual healthcare cost savings in the physically active group of 60%. In conclusion, physical activity reduces hypertension and the associated healthcare expenditure among community-dwelling elderly.